Sulfur-doped nh4v4o10 nanobelt cathode material for aqueous zinc-ion battery and preparation method and application thereof

CN117954580BActive Publication Date: 2026-10-30TIANJIN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410090567.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-23
Publication Date
2026-10-30
Estimated Expiration
2044-01-23

AI Technical Summary

Technical Problem

[0005]针对目前阻碍锌离子电池实际应用和产业化的问题,本发明以一种工艺简单、成本低廉的改性方法制备了锌离子电池的钒氧化物正极材料,应用于锌离子电池中可以同时解决上述正极的动力学和稳定性缺陷

Benefits of technology

[0021]硫化操作将硫离子与硫酸根离子掺入钒酸铵层间,作为层间支柱支撑钒酸铵的层状结构,并扩大了层间距,为锌离子的传输提供了宽阔的离子通道,使得电极的离子传输动力学加快并减小了离子传输对电极结构带来的应力应变,提高电极的结构稳定性。硫化使得钒酸铵的结构发生变形,使得钒酸铵的结晶度下降,无序度较高的结构能够为电解液的渗透提供各向异性的传输通道,且增加了电解液与电极之间的接触界面,有效地提高了电极的活性储存位点,并且无序结构有效地抑制了电极的体积变化,提升材料的稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117954580B_ABST
    Figure CN117954580B_ABST
Patent Text Reader

Abstract

This invention relates to sulfur-doped NH4V4O for use in aqueous zinc-ion batteries. 10 Nanoribbon cathode materials, their preparation methods, and applications: Ammonium metavanadate and oxalic acid monohydrate are dissolved in deionized water using a one-step hydrothermal method, then transferred to a hydrothermal reactor for hydrothermal treatment. The precipitate is collected, washed, and dried to obtain the precursor ammonium vanadate. Further, ammonium vanadate is sulfided and annealed with a sulfur source, thiourea, in a tube furnace to obtain sulfur-doped ammonium vanadate cathode materials. Sulfate ion groups and oxygen vacancies are simultaneously incorporated into the ammonium vanadate structure. It is assembled with sulfur-doped NH4V4O... 10 Aqueous zinc-ion batteries using nanoribbon cathode materials, at 0.2 A g ‑1 It has a discharge specific capacity of 331.2 mAh g. ‑1 At high magnification of 10A g ‑1 It still outputs 227.9mAh g. ‑1 Its high capacity, with a capacity retention rate of up to 89.36% after 5000 long cycles, surpasses most of the research results reported to date.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of aqueous zinc-ion battery technology. It relates to a strategy for a sulfur-doped ammonium vanadate material, and specifically to a method for preparing and applying a cathode material for aqueous zinc-ion batteries. Particularly, it relates to sulfur-doped NH4V4O for use in aqueous zinc-ion batteries. 10 Nanoribbon cathode materials, their preparation methods, and applications. Background Technology

[0002] With the increasing demand for energy storage technology and the lithium resource crisis, research and breakthroughs in non-lithium-ion batteries (such as sodium-ion, potassium-ion, magnesium-ion, zinc-ion, and aluminum-ion batteries) are particularly urgent. Among all lithium-ion battery alternatives, aqueous zinc-ion batteries are particularly valuable due to their high theoretical capacity and low redox potential (-0.76V vs. Zn / Zn). 2+ Zinc-ion batteries have been extensively studied due to their abundant natural reserves and low toxicity. Current research on cathode materials for zinc-ion batteries includes manganese-based materials (MnO2, Mn3O4, MnO), vanadium-based materials (V2O5, VO2, ZnV2O5), Prussian blue derivatives, and organic compounds. Manganese-based materials readily dissolve in aqueous electrolytes, causing structural decomposition and rapid capacity decay, while Prussian blue derivatives and organic compounds exhibit low intrinsic capacity. Vanadium-based oxides possess multiple oxidation states, which is beneficial for achieving high-capacity storage and high energy density. However, vanadium-based oxides still suffer from structural instability and slow reaction kinetics, bottlenecks that severely hinder their development. Because zinc ions have a large size and multiple charges, their movement in diffusion channels is more difficult, and they exhibit greater electrostatic forces with adjacent vanadium oxide layers, leading to sluggish zinc ion diffusion kinetics and negatively impacting battery reversibility. The stress generated during zinc ion entry and exit can also cause structural damage and even decomposition of vanadium oxides.

[0003] Current research on improving vanadium oxide cathodes includes nanostructure design, composite materials, and ion doping. Numerous reports have been published on nanoribbons, nanorods, three-dimensional nanoflowers, and other complex structures for nanostructuring. Nanostructuring increases the specific surface area of ​​the material and the contact area between the electrolyte and the electrode, increases the active sites for ion storage, and shortens the ion diffusion path. However, improvements in structural morphology do not address the inherent poor conductivity and structural stability of the material. Composites with carbon materials can further enhance the material's performance. Stable carbon materials help suppress the volume expansion of vanadium oxide during cycling, improving structural stability, and their good conductivity can enhance the overall conductivity of the composite material. However, carbon has a low capacity, and the introduction of carbon materials inevitably reduces the overall battery capacity.

[0004] While structural design and composite carbon materials can alleviate some performance defects in zinc-ion batteries, they cannot comprehensively improve the structural stability, ion diffusion kinetics, and reaction kinetics of the cathode. This severely hinders the practical application and industrialization of zinc-ion batteries. Numerous research findings on modified cathode materials have been reported, but few systematic designs can simultaneously improve both structural stability and reaction kinetics. This results in zinc-ion batteries being unable to operate stably for extended periods at high current densities and provide large charge-discharge capacities. Therefore, designing an efficient strategy to simultaneously address both the structural instability of cathode materials and slow reaction kinetics remains a pressing issue. Summary of the Invention

[0005] To address the current problems hindering the practical application and industrialization of zinc-ion batteries, this invention prepares vanadium oxide cathode materials for zinc-ion batteries using a simple and low-cost modification method. When applied to zinc-ion batteries, this method can simultaneously solve the aforementioned kinetic and stability defects of the cathode.

[0006] Unlike nanostructure design and carbon composites, introducing dopant ions and oxygen vacancies into vanadium oxides can modulate the lattice and electronic structures of the host material, improving structural stability, conductivity, and ion diffusion kinetics. Dopant ions, located between the material layers, act as interlayer "pillars" supporting the layered structure of the raw material and widen the interlayer spacing, providing a broad and convenient channel for zinc ion transport. This facilitates reversible zinc ion transport within the material structure and improves ion transport kinetics. Furthermore, the increased interlayer spacing suppresses the volume changes caused by zinc ion insertion / extraction on the cathode material structure, reducing stress and strain and the possibility of structural damage, thus improving the material's cycle stability. Positively charged zinc ions are easily attracted by the electrostatic attraction of oxygen atoms in adjacent vanadium oxide layers during transport, leading to slow transport or trapping within the structure and preventing successful insertion / extraction. Introducing oxygen vacancies into the structure alleviates the electrostatic effect of oxygen atoms on zinc ions, effectively promoting zinc ion transport and improving the material's ion transport kinetics and reversibility. Simultaneously, dopant ions and oxygen vacancies can modulate the electronic structure of the material, increasing its intrinsic conductivity and further enhancing reaction kinetics. Therefore, this invention, based on the structural control theory of ion and oxygen vacancy doping, simultaneously incorporates sulfate ion groups and oxygen vacancies into the ammonium vanadate structure through a sulfidation process. First, the negative charge of the sulfate group allows it to electrostatically bind the movement of intrinsic interlayer ammonium ions in ammonium vanadate, enhancing the structural stability of the matrix material. Second, the introduction of oxygen vacancies suppresses the electrostatic interaction of oxygen atoms on energy storage ions, lowering the diffusion barrier of zinc ions. Furthermore, the incorporation of sulfate and oxygen vacancies causes a certain degree of crystal structure deformation, reducing the long-range order and increasing the amorphousness of the structure. This provides anisotropic channels for electrolyte transport, facilitating rapid transport and penetration of the electrolyte within the material and enhancing ion diffusion kinetics. Sulfate and oxygen vacancies, acting as electron donors, can provide additional capacity during energy storage, enabling the battery to output higher energy density.

[0007] Specifically, ammonium metavanadate and oxalic acid monohydrate are dissolved in deionized water by a one-step hydrothermal method and then transferred to a hydrothermal reactor for hydrothermal treatment. The precipitate is collected, washed, and dried to obtain the precursor ammonium vanadate. The ammonium vanadate is then further subjected to sulfurization annealing with the sulfur source thiourea in a tube furnace to obtain sulfur-doped ammonium vanadate cathode material.

[0008] Introducing sulfide and sulfate ions, as well as oxygen vacancies, into vanadium oxide through sulfidation can simultaneously improve structural stability and reaction kinetics, specifically increasing the battery's capacity density. The modified cathode exhibits excellent rate performance and maintains high capacity retention even after long cycling. A zinc-ion battery assembled with the cathode material provided by this invention achieves a capacity density of 0.2 Ag... -1 It has a discharge specific capacity of 331.2 mAh g. -1 ; at high magnification 10Ag-1 It still output 227.9mAh g. -1 The material exhibits high capacity, with a capacity retention of up to 89.36% after 5000 cycles, demonstrating outstanding rate performance and cycling stability. This indicates that the ion transport kinetics and structural stability of the sulfided material are effectively improved, and its electrochemical performance surpasses most previously reported research findings. Based on the research results reported by Quan et al., NH4V4O... 10 In 5A g -1 The capacity is only 95mAh g -1 Furthermore, the capacity decay is extremely severe, at 2Ag -1 After 1000 cycles, the capacity retention rate is only about 40%.

[0009] The technical solution of the present invention is as follows:

[0010] Sulfur-doped NH4V4O for use in aqueous zinc-ion batteries 10 Nanoribbon cathode material; ammonium vanadate structure is simultaneously doped with sulfate ion groups and oxygen vacancies.

[0011] The present invention relates to sulfur-doped NH4V4O for aqueous zinc-ion batteries. 10 The preparation method of nanoribbon cathode material includes the following steps:

[0012] 1): Preparation of NH4V4O 10 Nanoribbon precursor: Weigh NH4VO3 powder and oxalic acid monohydrate granules and dissolve them in deionized water. Stir under water bath heating until the solution is clear and transparent. After the solution is allowed to stand and cool, add ammonia water dropwise and adjust the pH to 8.0-10.0 using a pH meter. Then transfer the mixed solution to a hydrothermal reactor, tighten the reactor, and place it in a forced-air drying oven for hydrothermal treatment for 4-12 hours. After naturally cooling to room temperature, open the hydrothermal reactor, pour out the supernatant, and collect the precipitate at the bottom of the reactor. Wash the precipitate with water and ethanol respectively, and then dry it thoroughly in a vacuum drying oven to obtain NH4VO3. 10 Nanoribbon precursors;

[0013] 2): Preparation of sulfur-doped NH4V4O 10 Nanoribbon cathode material: Weigh the NH4V4O obtained in step 1). 10 The nanoribbon precursor was placed on one side of an alumina boat, while thiourea powder was placed on the other side. The boat was then capped and placed inside a tube furnace, with one side of the thiourea powder facing upwind and the other downwind. The tube furnace was then purged to fill it with an inert atmosphere, which was continuously circulated. After the furnace cooled naturally, the sulfur-doped NH4V4O2 was removed. 10 Nanoribbon cathode material.

[0014] In step 1), the molar ratio of raw material NH4VO3 to oxalic acid monohydrate is 1:0.8-2. After dissolving in deionized water by water bath heating, the concentration of NH4VO3 is 0.05-0.15 mol / L. -1 .

[0015] In step 1), the hydrothermal temperature is 140-180℃, and the hydrothermal time is maintained for 4-12 hours after the temperature is raised to the specified temperature; preferably 6 hours.

[0016] In step 1), the centrifuge speed for centrifuging to wash the precipitate is 7500 r / min. -1 For the above, the single centrifugation time should be at least 3 minutes; the vacuum drying temperature should be above 40℃, and the drying time should be at least 8 hours.

[0017] In step 2), thiourea: sulfur-doped NH4V4O 10 The mass ratio of the nanoribbon cathode material is 0.5 to 4:1, and the calcination atmosphere is ammonia or nitrogen.

[0018] In step 2), the gas flow rate during calcination is controlled below 200 sccm, the heat preservation temperature of the tubular furnace is 260-350℃, and the heat preservation time is more than 1 hour; preferably 1-4 hours.

[0019] The sulfur-doped NH4V4O of the present invention 10 Sulfur-doped NH4V4O nanoribbon cathode material for aqueous zinc-ion batteries 10 Nanoribbon cathode material; the prepared sulfur-doped ammonium vanadate cathode material is used in battery assembly. The obtained cathode material is mixed with carbon black conductive agent and polyvinylidene fluoride in a certain proportion to form a uniform slurry, which is then coated onto titanium foil and cut into circular cathode electrode sheets. These sheets, along with separators and lithium sheets, are then used to assemble button batteries. The cathode material is equipped with sulfur-doped NH4V4O 10 Aqueous zinc-ion batteries using nanoribbon cathode materials, at 0.2 A g -1 It has a discharge specific capacity of 331.2 mAh g. -1 At high magnification of 10A g -1 It still output 227.9mAh g. -1 It has a high capacity, and its capacity retention rate is as high as 89.36% after 5000 long cycles.

[0020] Compared with the prior art, the beneficial effects of the present invention are:

[0021] The sulfidation process incorporates sulfur and sulfate ions into the interlayer space of ammonium vanadate, acting as interlayer pillars to support its layered structure and widening the interlayer spacing. This provides a broad ion channel for zinc ion transport, accelerating ion transport kinetics and reducing stress and strain on the electrode structure, thus improving structural stability. Sulfidation also deforms the structure of ammonium vanadate, reducing its crystallinity. The higher degree of disorder provides anisotropic transport channels for electrolyte penetration and increases the contact interface between the electrolyte and the electrode, effectively enhancing the active storage sites. Furthermore, the disordered structure effectively suppresses volume changes in the electrode, improving material stability.

[0022] The reducing sulfur gas generated during sulfidation introduces oxygen vacancies into the ammonium vanadate. These oxygen vacancies effectively suppress the electrostatic attraction between zinc ions and oxygen atoms in the adjacent vanadium-oxygen layer during zinc ion transport, reducing the transport resistance of zinc ions and increasing the conductivity of ammonium vanadate, thereby enhancing the reaction kinetics of the electrode.

[0023] This invention leverages the advantages of the sulfidation mechanism to introduce sulfur-doped ions and oxygen vacancies into the ammonium vanadate structure, effectively improving the reversible specific capacity of zinc-ion batteries and endowing them with excellent long-term cycle stability and rate performance. It is equipped with sulfur-doped NH4V4O 10 Aqueous zinc-ion batteries using nanoribbon cathode materials, at 0.2 A g -1 It has a discharge specific capacity of 331.2 mAh g. -1 At high magnification of 10A g -1 It still outputs 227.9mAh g. -1 The high capacity, with a capacity retention of up to 89.36% after 5000 cycles, surpasses most reported research results. This novel strategy also provides inspiration for the rational design of other emerging energy storage applications. A literature search revealed that the sulfur-doped NH4V4O proposed in this invention can be applied to aqueous zinc-ion batteries. 10 The preparation method of nanoribbon cathode materials has not been publicly reported. Attached Figure Description

[0024] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below.

[0025] Figure 1 The sulfur-doped NH4V4O prepared in Example 1 of this invention 10 XRD pattern of nanoribbon cathode material;

[0026] Figure 2 The NH4V4O prepared in Example 1 of this invention 10 SEM image of the nanoribbon precursor;

[0027] Figure 3 The sulfur-doped NH4V4O prepared in Example 1 of this invention 10 SEM image of nanoribbon cathode material;

[0028] Figure 4 The sulfur-doped NH4V4O prepared in Example 1 of this invention 10 TEM image of nanoribbon cathode material;

[0029] Figure 5 The sulfur-doped NH4V4O prepared in Example 1 of this invention 10 Rate performance test data and comparison of zinc-ion batteries assembled with nanoribbon cathode materials;

[0030] Figure 6 The sulfur-doped NH4V4O prepared in Example 1 of this invention 10 Zinc-ion batteries assembled with nanoribbon cathode materials and NH4V4O 10 Test data and comparison of rate performance of zinc-ion batteries assembled from different materials;

[0031] Figure 7 The sulfur-doped NH4V4O prepared in Example 1 of this invention 10 Cycle performance test data and comparison of zinc-ion batteries assembled with nanoribbon cathode materials. Detailed Implementation

[0032] The technical solution of the present invention will be described in detail below with reference to specific embodiments. The embodiments given are only for explaining the present invention and are not intended to limit the scope of the invention. Unless otherwise defined, all technical and scientific terms used herein have the meaning commonly understood by one of ordinary skill in the art.

[0033] This invention proposes a strategy for cathode materials in aqueous zinc-ion batteries and provides a high-performance sulfur-doped ammonium vanadate material, the preparation method of which includes the following steps:

[0034] 1): Synthesis of NH4V4O 10 Nanoribbon precursor: NH4VO3 and oxalic acid monohydrate were dissolved in ultrapure water under stirring. The solution was stirred until clear and transparent under water bath heating. After cooling, ammonia was added dropwise and the pH was adjusted to 8.0–10.0 using a pH meter. The mixed solution was then transferred to a hydrothermal reactor, sealed, and hydrothermally heated in a forced-air drying oven for 4–12 hours. After cooling, the precipitate in the hydrothermal reactor was collected, washed repeatedly with ultrapure water and anhydrous ethanol, and then dried in a vacuum drying oven to obtain NH4V4O. 10 Nanoribbon precursors;

[0035] 2): Preparation of sulfur-doped NH4V4O 10 Nanoribbon cathode material: NH4V4O prepared in step 1) 10 The nanoribbon precursor and thiourea were placed on opposite sides of an alumina boat, with the thiourea positioned upwind. Sulfidation was then performed in a quartz tube furnace to obtain sulfur-doped NH4V4O. 10 Nanoribbon cathode materials;

[0036] The sulfur-doped NH4V4O described in this embodiment 10 The preparation method for nanoribbon cathode materials employs a solvothermal method and a one-step sulfurization annealing method. This method is simple, operates under mild reaction conditions, uses inexpensive raw materials, and is environmentally friendly and pollution-free. Sulfur is doped into NH4V4O... 10 Nanoribbon cathode materials are used in aqueous zinc-ion batteries. The lattice deformation, sulfur-based ions, and oxygen vacancy doping after sulfidation can improve the transport kinetics of zinc ions, enhance the conductivity of the electrode material, and suppress the zinc ion intercalation / deintercalation reaction with NH4V4O3. 10 The volume changes caused by the structure improve the structural stability of the electrode. This effectively increases the reversible specific capacity of the zinc-ion battery, demonstrating long-term cycle stability and rate performance.

[0037] Specifically, in step 1), the ratio of raw material NH4VO3 to oxalic acid monohydrate is 1:0.8-2 (molar ratio), and the concentration of NH4VO3 after dissolving in deionized water in a water bath is 0.05-0.15 mol / L. -1 Add ammonia dropwise until the pH reaches 8.0–10.0. The hydrothermal temperature is 140–180℃, and the hydrothermal time is 4–12 hours, preferably 6 hours. The centrifuge speed for washing the precipitate is 7500 rpm. -1 For the above, the single centrifugation time should be at least 3 minutes; the vacuum drying temperature should be above 40℃, and the drying time should be at least 8 hours.

[0038] Specifically, in step 2), thiourea: sulfur-doped NH4V4O 10 The ratio of nanoribbon cathode material is 0.5 to 4:1 (mass ratio). The calcination atmosphere is ammonia or nitrogen, the gas flow rate is controlled below 200 sccm, the holding temperature is 260 to 350℃, and the holding time is more than 1 hour.

[0039] Based on the above embodiments, the present invention provides the following sulfur-doped NH4V4O 10 Specific embodiments of nanoribbon cathode materials and their preparation methods.

[0040] Example 1:

[0041] 1): Synthesis of NH4V4O 10Nanoribbon precursor. NH₄VO₃ and oxalic acid monohydrate were dissolved and stirred in ultrapure water under a water bath until the solution became clear and transparent. Ammonia was added dropwise until the pH reached 9.0, and the NH₄VO₃ concentration was 0.1 mol / L. -1 The concentration of oxalic acid monohydrate is 0.1 mol / L. -1 Then transfer the solution to a hydrothermal reactor until it is 80% full, and keep it in a 160℃ drying oven for 6 hours. After cooling to room temperature, open the reactor, pour off the clear solution from the top layer, and collect the precipitate from the bottom. Centrifuge the precipitate separately with deionized water and anhydrous ethanol at a speed of 8000 rpm. -1 Centrifuge for 5 minutes, then place in a vacuum drying oven and dry at 60°C for 12 hours to obtain NH4V4O. 10 Nanoribbon precursor.

[0042] 2): Preparation of sulfur-doped NH4V4O 10 Nanoribbon cathode material. Weigh out NH4V4O in a mass ratio of 1:1. 10 Nanoribbon precursors and thiourea were placed on the downwind side of a tube furnace and the upwind side of a tube furnace. After three gas scrubbing processes, the temperature was raised to 300℃ and held for 2 hours at a gas flow rate of 80 scmm. After cooling, the powder was removed to obtain sulfur-doped NH4V4O. 10 Nanoribbon cathode material.

[0043] Prepared sulfur-doped NH4V4O 10 Nanoribbon cathode materials are used in battery assembly. Sulfur-doped NH4V4O 10 Nanoribbon cathode material, carbon black conductive agent, and polyvinylidene fluoride were thoroughly ground at a mass ratio of 8:1:1, and then NMP solution was added and continuously magnetically stirred for 8 hours. The uniformly dispersed, viscous slurry was coated onto titanium foil and dried in a vacuum drying oven at 60°C for 12 hours. The dried material was then cut into circular cathode electrode sheets with a diameter of approximately 12 mm, weighed, and set aside. The areal density of the active material on the electrode sheets was 1.5 mg / cm³. -2 Then, the sulfur-doped NH4V4O prepared... 10 Nanoribbon positive electrode material, glass fiber separator, lithium negative electrode and zinc trifluorosulfonate aqueous electrolyte were assembled into a 2032 type button zinc-ion battery. The amount of electrolyte added to the positive electrode side was 15 μl and the amount added to the negative electrode side was 10 μl. The assembled battery was placed in a constant temperature chamber at 25℃ for 12 h before electrochemical testing was performed.

[0044] The product prepared in Example 1 is sulfur-doped NH4V4O 10 Taking nanoribbon cathode materials as an example, analysis using X-ray diffraction revealed, for instance... Figure 1 As shown, sulfur-doped NH4V4O 10The X-ray diffraction (XRD) pattern of the nanoribbon cathode material shows weak NH4V4O 10 The diffraction peak (JCPDS: 75-0325) indicates that the material has a stable crystal structure and high product purity. The absence of sulfur-related peaks indicates that no sulfur byproducts were generated.

[0045] like Figure 2 As shown, NH4V4O can be observed using scanning electron microscopy (SEM). 10 The precursor morphology of the nanoribbon is a nanoribbon; such as Figure 3 As shown, NH4V4O is doped with sulfur. 10 Scanning electron microscopy (SEM) imaging of nanoribbon cathode materials reveals sulfur-doped NH4V4O 10 The morphology of the nanoribbon cathode material is fragmented nanoribbons. (Combined) Figure 4 Transmission electron microscopy (TEM) imaging and elemental distribution analysis confirmed the presence of sulfur doping in NH4V4O. 10 Successful preparation of nanoribbon cathode materials and uniform doping with sulfur.

[0046] like Figure 5 The image shows an assembly of sulfur-doped NH4V4O. 10 Zinc-ion batteries with nanoribbon cathode materials under different currents (0.2Ag) -1 0.4A g -1 0.6A g -1 0.8A g -1 1.0A g -1 5A g -1 The constant current charge-discharge (GCD) test data of ) Figure 6 The image shows sulfur-doped NH4V4O 10 Rate performance of nanoribbon cathode materials, sulfur-doped NH4V4O 10 Nanoribbon cathode materials at 0.2, 0.4, 0.6, 0.8, 1.0, and 5.0 A g -1 It showed 331.2 mA hg -1 326.0mA hg -1 318.2mAh g -1 310.0mA hg -1 291.3mA hg -1 247.5mA hg -1 The high discharge specific capacity, when the rate recovers to 0.2A g -1 The capacity can be restored to 334mAh g. -1 This demonstrates good rate capability and reversibility, indicating that sulfur-doped NH4V4O 10Nanoribbon cathode materials possess rapid reaction kinetics and structural stability; according to research results reported by Quan et al., NH4V4O 10 In 5Ag -1 The capacity is only 95mAh g -1 .

[0047] like Figure 7 The image shows an assembly of sulfur-doped NH4V4O. 10 Zinc-ion batteries using nanoribbon cathode materials at 10 A g -1 Cyclic test data at current density. At 10Ag -1 Even after 5000 cycles at high current density, it still exhibits a capacity of 227.9 mAh g. -1 The discharge specific capacity and capacity retention rate of 89.36% exceed most currently reported zinc-ion battery studies, indicating that the battery can maintain excellent charge-discharge performance even under high current, demonstrating its excellent reaction kinetics and structural stability. Based on the research results reported by Quan et al., NH4V4O 10 The capacity decay is very severe, at 2A g -1 After 1000 cycles, the capacity retention rate was only about 40%, indicating severe capacity decay.

[0048] Example 2:

[0049] 1): Synthesis of NH4V4O 10 Nanoribbon precursor. NH₄VO₃ and oxalic acid monohydrate were dissolved and stirred in ultrapure water under a water bath until the solution became clear and transparent. Ammonia was added dropwise until the pH reached 9.5, and the NH₄VO₃ concentration was 0.1 mol / L. -1 The concentration of oxalic acid monohydrate is 0.1 mol / L. -1 Then transfer the solution to a hydrothermal reactor until it is 80% full, and keep it in a 160℃ drying oven for 4 hours. After cooling to room temperature, open the reactor, pour off the clear solution from the top layer, and collect the precipitate from the bottom. Centrifuge the precipitate separately with deionized water and anhydrous ethanol at a speed of 8500 rpm. -1 Centrifuge for 3 minutes, then place in a vacuum drying oven and dry at 70°C for 12 hours to obtain NH4V4O. 10 Nanoribbon precursor.

[0050] 2): Preparation of sulfur-doped NH4V4O 10 Nanoribbon cathode material. Weigh out NH4V4O in a mass ratio of 1:3. 10Nanoribbon precursors and thiourea were placed on the downwind side of a tube furnace and the upwind side of a tube furnace. After three gas scrubbing processes, the temperature was raised to 350℃ and held for 2 hours at a gas flow rate of 90 scmm. After cooling, the powder was removed to obtain sulfur-doped NH4V4O. 10 Nanoribbon cathode material.

[0051] Prepared sulfur-doped NH4V4O 10 Nanoribbon cathode materials are used in battery assembly. Sulfur-doped NH4V4O 10 Nanoribbon cathode material, carbon black conductive agent, and polyvinylidene fluoride were thoroughly ground at a mass ratio of 8:1:1, and then NMP solution was added and continuously magnetically stirred for 8 hours. The uniformly dispersed, viscous slurry was coated onto titanium foil and dried in a vacuum drying oven at 60°C for 12 hours. The dried material was then cut into circular cathode electrode sheets with a diameter of approximately 12 mm, weighed, and set aside. The areal density of the active material on the electrode sheets was 1.5 mg / cm³. -2 Then, the sulfur-doped NH4V4O prepared... 10 Nanoribbon positive electrode material, glass fiber separator, lithium negative electrode and zinc trifluorosulfonate aqueous electrolyte were assembled into a 2032 type button zinc-ion battery. The amount of electrolyte added to the positive electrode side was 15 μl and the amount added to the negative electrode side was 10 μl. The assembled battery was placed in a constant temperature chamber at 25℃ for 12 h before electrochemical testing was performed.

[0052] Sulfur-doped NH4V4O 10 Nanoribbon cathode materials at 0.2, 0.4, 0.6, 0.8, 1.0, and 5.0 A g -1 It showed 286.4 mA hg -1 277.3mA hg -1 259.6mA hg -1 231.2mA hg -1 210.8mA hg -1 157.4mA hg -1 The high discharge specific capacity, when the rate recovers to 0.2A g -1 The capacity can be restored to 251.3mAh g. -1 According to research results reported by Quan et al., NH4V4O 10 In 5A g -1 The capacity is only 95mAh g -1 .

[0053] Equipped with sulfur-doped NH4V4O 10 Zinc-ion batteries using nanoribbon cathode materials at 10 A g -1 It exhibits a current density of 121.7 mA hg. -1The discharge specific capacity was [not specified], and the capacity retention rate after 4000 cycles was 69.36%. Based on the research results reported by Quan et al., NH4V4O [is mentioned]. 10 The capacity decay is very severe, at 2A g -1 After 1000 cycles, the capacity retention rate was only about 40%, indicating severe capacity decay.

[0054] Example 3:

[0055] 1): Synthesis of NH4V4O 10 Nanoribbon precursor. NH₄VO₃ and oxalic acid monohydrate were dissolved and stirred in ultrapure water under a water bath until the solution became clear and transparent. Ammonia was added dropwise until the pH reached 10.0, and the NH₄VO₃ concentration was 0.05 mol / L. -1 The concentration of oxalic acid monohydrate is 0.04 mol / L. -1 Then transfer the solution to a hydrothermal reactor until it is 80% full, and keep it in a 140℃ drying oven for 8 hours. After cooling to room temperature, open the reactor, pour off the clear solution from the top layer, and collect the precipitate from the bottom. Centrifuge the precipitate separately with deionized water and anhydrous ethanol at a speed of 8000 rpm. -1 Centrifuge for 7 minutes, then dry in a vacuum drying oven at 60°C for 24 hours to obtain NH4V4O. 10 Nanoribbon precursor.

[0056] 2): Preparation of sulfur-doped NH4V4O 10 Nanoribbon cathode material. Weigh out NH4V4O in a mass ratio of 1:4. 10 Nanoribbon precursors and thiourea were placed on the downwind side of a tube furnace and the upwind side of a tube furnace. After three gas scrubbing processes, the temperature was raised to 260℃ and held for 4 hours at a gas flow rate of 100 scmm. After cooling, the powder was removed to obtain sulfur-doped NH4V4O. 10 Nanoribbon cathode material.

[0057] Prepared sulfur-doped NH4V4O 10 Nanoribbon cathode materials are used in battery assembly. Sulfur-doped NH4V4O 10 Nanoribbon cathode material, carbon black conductive agent, and polyvinylidene fluoride were thoroughly ground at a mass ratio of 8:1:1, and then NMP solution was added and continuously magnetically stirred for 8 hours. The uniformly dispersed, viscous slurry was coated onto titanium foil and dried in a vacuum drying oven at 70°C for 12 hours. The dried material was then cut into circular cathode electrode sheets with a diameter of approximately 12 mm, weighed, and set aside. The areal density of the active material on the electrode sheets was 1.5 mg / cm³. -2 Then, the sulfur-doped NH4V4O prepared... 10Nanoribbon positive electrode material, glass fiber separator, lithium negative electrode and zinc trifluorosulfonate aqueous electrolyte were assembled into a 2032 type button zinc-ion battery. The amount of electrolyte added to the positive electrode side was 15 μl and the amount added to the negative electrode side was 10 μl. The assembled battery was placed in a constant temperature chamber at 25℃ for 12 h before electrochemical testing was performed.

[0058] Sulfur-doped NH4V4O 10 Nanoribbon cathode materials at 0.2, 0.4, 0.6, 0.8, 1.0, and 5.0 A g -1 It showed 300.7 mA hg -1 295.6mA hg -1 289.9mA hg -1 280.2mA hg -1 273.5mA hg -1 210.6mA hg -1 The high discharge specific capacity, when the rate recovers to 0.2A g -1 The capacity can be restored to 290.4mAh g. -1 According to research results reported by Quan et al., NH4V4O 10 In 5A g -1 The capacity is only 95mAh g -1 .

[0059] Equipped with sulfur-doped NH4V4O 10 Zinc-ion batteries using nanoribbon cathode materials at 10 A g -1 It exhibits 178.4 mA hg after 5000 cycles at high current density. -1 The discharge specific capacity was 77.21%, with a capacity retention rate of 77.21%. Based on research results reported by Quan et al., NH4V4O... 10 The capacity decay is very severe, at 2A g -1 After 1000 cycles, the capacity retention rate was only about 40%, indicating severe capacity decay.

[0060] Example 4:

[0061] 1): Synthesis of NH4V4O 10 Nanoribbon precursor. NH₄VO₃ and oxalic acid monohydrate were dissolved and stirred in ultrapure water under a water bath until the solution became clear and transparent. Ammonia was added dropwise until the pH reached 8.0, and the NH₄VO₃ concentration was 0.15 mol / L. -1 The concentration of oxalic acid monohydrate is 0.30 mol / L. -1Then transfer the solution to a hydrothermal reactor until it is 80% full, and keep it in a 140℃ drying oven for 12 hours. After cooling to room temperature, open the reactor, pour out the clear solution, and collect the precipitate at the bottom. Clean the precipitate with deionized water and anhydrous ethanol by centrifugation at 9000 rpm. -1 Centrifuge for 4 minutes, then dry in a vacuum drying oven at 90°C for 8 hours to obtain NH4V4O. 10 Nanoribbon precursor.

[0062] 2): Preparation of sulfur-doped NH4V4O 10 Nanoribbon cathode material. Weigh out NH4V4O in a mass ratio of 1:0.5. 10 Nanoribbon precursors and thiourea were placed on the downwind side of a tube furnace and the upwind side of a tube furnace. After four gas scrubbing cycles, the temperature was raised to 350℃ and held for 4 hours at a gas flow rate of 120 sccm. After cooling, the powder was removed to obtain sulfur-doped NH4V4O. 10 Nanoribbon cathode material.

[0063] Prepared sulfur-doped NH4V4O 10 Nanoribbon cathode materials are used in battery assembly. Sulfur-doped NH4V4O 10 Nanoribbon cathode material, carbon black conductive agent, and polyvinylidene fluoride were thoroughly ground at a mass ratio of 8:1:1, and then NMP solution was added and continuously stirred magnetically for 8 hours. The uniformly dispersed, viscous slurry was coated onto titanium foil and dried in a vacuum drying oven at 60°C for 16 hours. The dried material was then cut into circular cathode electrode sheets with a diameter of approximately 12 mm, weighed, and set aside. The areal density of the active material on the electrode sheets was 1.5 mg / cm³. -2 Then, the sulfur-doped NH4V4O prepared... 10 Nanoribbon cathode material, glass fiber separator, lithium anode, and zinc trifluorosulfonate aqueous electrolyte were used to assemble a 2032 model button zinc-ion battery. 15 μl of electrolyte was added to the cathode side and 10 μl to the anode side. The assembled battery was incubated at 25°C for 12 hours before electrochemical testing. The battery was also equipped with sulfur-doped NH4V4O4. 10 Zinc-ion batteries with nanoribbon cathode materials under different currents (0.2 A g) -1 0.4A g -1 0.6A g -1 0.8Ag -1 1.0A g -1 5A g -1 It showed 321.2 mA hg -1 311.0mA hg -1 302.2mA hg -1 289.8mAh g-1 280.3mA hg -1 211.6mA hg -1 The discharge specific capacity, when the rate recovers to 0.2A g -1 The capacity can be restored to 319.3mAh g. -1 This demonstrates good rate capability and reversibility, indicating that sulfur-doped NH4V4O 10 Nanoribbon cathode materials possess rapid ion diffusion kinetics and structural stability; according to research results reported by Quan et al., NH4V4O 10 In 5A g -1 The capacity is only 95mAh g -1 .

[0064] Equipped with sulfur-doped NH4V4O 10 Zinc-ion batteries using nanoribbon cathode materials at 10 A g -1 The capacity retention rate after 5000 cycles at the current density is 90.3%, exceeding most currently reported studies on zinc-ion batteries, indicating that this battery can maintain excellent charge-discharge performance even at high currents. Based on the research results reported by Quan et al., NH4V4O 10 The capacity decay is very severe, at 2A g -1 After 1000 cycles, the capacity retention rate was only about 40%, indicating severe capacity decay.

[0065] Example 5:

[0066] 1): Synthesis of NH4V4O 10 Nanoribbon precursor. NH₄VO₃ and oxalic acid monohydrate were dissolved and stirred in ultrapure water under a water bath until the solution became clear and transparent. Ammonia was added dropwise until the pH reached 10.0, and the NH₄VO₃ concentration was 0.05 mol / L. -1 The concentration of oxalic acid monohydrate is 0.1 mol / L. -1 Then transfer the solution to a hydrothermal reactor until it is 80% full, and incubate it in a 180°C drying oven for 6 hours. After cooling to room temperature, open the reactor, pour out the clear solution, and collect the precipitate at the bottom. Centrifuge the precipitate separately with deionized water and anhydrous ethanol at a speed of 10,000 rpm. -1 Centrifuge for 5 minutes, then place in a vacuum drying oven and dry at 50°C for 36 hours to obtain NH4V4O. 10 Nanoribbon precursor.

[0067] 2): Preparation of sulfur-doped NH4V4O 10 Nanoribbon cathode material. Weigh out NH4V4O in a mass ratio of 1:2.5. 10Nanoribbon precursors and thiourea were placed on the downwind side of a tube furnace and the upwind side of a tube furnace. After three gas scrubbing processes, the temperature was raised to 320℃ and held for 2 hours at a gas flow rate of 150 sccm. After cooling, the powder was removed to obtain sulfur-doped NH4V4O. 10 Nanoribbon cathode material.

[0068] Prepared sulfur-doped NH4V4O 10 Nanoribbon cathode materials are used in battery assembly. Sulfur-doped NH4V4O 10 Nanoribbon cathode material, carbon black conductive agent, and polyvinylidene fluoride were thoroughly ground at a mass ratio of 8:1:1, and then NMP solution was added and continuously magnetically stirred for 8 hours. The uniformly dispersed, viscous slurry was coated onto titanium foil and dried in a vacuum drying oven at 60°C for 24 hours. The resulting material was cut into circular cathode electrode sheets with a diameter of approximately 12 mm, weighed, and set aside. The areal density of the active material on the electrode sheets was 1.5 mg / cm³. -2 Then, the sulfur-doped NH4V4O prepared... 10 Nanoribbon cathode material, glass fiber separator, lithium anode, and zinc trifluorosulfonate aqueous electrolyte were used to assemble a 2032 model button zinc-ion battery. 15 μl of electrolyte was added to the cathode side and 10 μl to the anode side. The assembled battery was incubated at 25°C for 12 hours before electrochemical testing. The battery was also equipped with sulfur-doped NH4V4O4. 10 Zinc-ion batteries with nanoribbon cathode materials under different currents (0.2 A g) -1 0.4A g -1 0.6A g -1 0.8Ag -1 1.0A g -1 5Ag -1 It showed 332.5 mA hg -1 324.6mA hg -1 315.3mA hg -1 306.6mAh g -1 288.9mA hg -1 235.0mA hg -1 The high discharge specific capacity, when the rate recovers to 0.2A g -1 The capacity can be restored to 330mAh g. -1 This demonstrates good rate capability and reversibility, indicating that sulfur-doped NH4V4O 10 Nanoribbon cathode materials possess rapid ion diffusion kinetics and structural stability; according to research results reported by Quan et al., NH4V4O 10 In 5A g -1 The capacity is only 95mAh g-1 .

[0069] like Figure 6 The image shows an assembly of sulfur-doped NH4V4O. 10 Zinc-ion batteries using nanoribbon cathode materials at 10 A g -1 Cyclic test data at current density. At 10A g -1 After 5000 cycles at high current density, the capacity retention rate was 88.42%, exceeding most currently reported studies on zinc-ion batteries, indicating that this battery can maintain excellent charge-discharge performance even at high current. Based on the research results reported by Quan et al., NH4V4O 10 The capacity decay is very severe, at 2A g -1 After 1000 cycles, the capacity retention rate was only about 40%, indicating severe capacity decay.

[0070] Example 6:

[0071] 1): Synthesis of NH4V4O 10 Nanoribbon precursor. NH₄VO₃ and oxalic acid monohydrate were dissolved and stirred in ultrapure water under a water bath until the solution became clear and transparent. Ammonia was added dropwise until the pH reached 8.5, and the NH₄VO₃ concentration was 0.15 mol / L. -1 The concentration of oxalic acid monohydrate is 0.13 mol / L. -1 Then transfer the solution to a hydrothermal reactor until it is 80% full, and incubate it in a 170°C drying oven for 4 hours. After cooling to room temperature, open the reactor, pour out the clear solution, and collect the precipitate at the bottom. Centrifuge the precipitate separately with deionized water and anhydrous ethanol at a speed of 8200 rpm. -1 The solution was dried in a vacuum drying oven at 40°C for 48 hours for 8 minutes to obtain NH4V4O. 10 Nanoribbon precursor.

[0072] 2): Preparation of sulfur-doped NH4V4O 10 Nanoribbon cathode material. Weigh out NH4V4O in a mass ratio of 1:1.5. 10 Nanoribbon precursors and thiourea were placed on the lower air vent side of a tube furnace, and thiourea on the upper air vent side. After gas purging, the temperature was raised to 260℃ and held for 3 hours at a gas flow rate of 180 sccm. After cooling, the powder was removed to obtain sulfur-doped NH4V4O. 10 Nanoribbon cathode material.

[0073] Prepared sulfur-doped NH4V4O 10 Nanoribbon cathode materials are used in battery assembly. Sulfur-doped NH4V4O 10Nanoribbon cathode material, carbon black conductive agent, and polyvinylidene fluoride were thoroughly ground at a mass ratio of 8:1:1, and then NMP solution was added and continuously magnetically stirred for 8 hours. The uniformly dispersed, viscous slurry was coated onto titanium foil and dried in a vacuum drying oven at 70°C for 12 hours. The resulting slurry was cut into circular cathode electrode sheets with a diameter of approximately 12 mm, weighed, and set aside. The areal density of the active material on the electrode sheets was 1.5 mg / cm³. -2 Then, the sulfur-doped NH4V4O prepared... 10 Nanoribbon cathode material, glass fiber separator, lithium anode, and zinc trifluorosulfonate aqueous electrolyte were used to assemble a 2032 model button zinc-ion battery. 15 μl of electrolyte was added to the cathode side and 10 μl to the anode side. The assembled battery was incubated at 25°C for 12 hours before electrochemical testing. The battery was also equipped with sulfur-doped NH4V4O4. 10 Zinc-ion batteries with nanoribbon cathode materials under different currents (0.2 A g) -1 0.4Ag -1 0.6Ag -1 0.8Ag -1 1.0Ag -1 5Ag -1 It showed 330.2 mA hg -1 318.3mA hg -1 310.2mA hg -1 298.9mA hg -1 287.6mAh g -1 233.3mA hg -1 The high discharge specific capacity, when the rate recovers to 0.2Ag -1 The capacity can be restored to 328.3mAh g. -1 This demonstrates good rate capability and reversibility, indicating that sulfur-doped NH4V4O 10 Nanoribbon cathode materials possess rapid ion diffusion kinetics and structural stability; according to research results reported by Quan et al., NH4V4O 10 In 5Ag -1 The capacity is only 95mAh g -1 .

[0074] Equipped with sulfur-doped NH4V4O 10 Zinc-ion batteries with nanoribbon cathode materials at 10Ag -1 After 5000 cycles at the current density, the capacity retention rate was 89.03%, exceeding most currently reported studies on zinc-ion batteries, indicating that this battery can maintain excellent charge-discharge performance even under high current. Based on the research results reported by Quan et al., NH4V4O 10The capacity decay is very severe, at 2Ag -1 After 1000 cycles, the capacity retention rate was only about 40%, indicating severe capacity decay.

[0075] Example 7:

[0076] 1): Synthesis of NH4V4O 10 Nanoribbon precursor. NH₄VO₃ and oxalic acid monohydrate were dissolved and stirred in ultrapure water at 60°C until the solution became clear and transparent. Ammonia was added dropwise until the pH reached 9.5, and the NH₄VO₃ concentration was 0.15 mol / L. -1 The concentration of oxalic acid monohydrate is 0.225 mol / L. -1 Then transfer the solution to a hydrothermal reactor until it is 80% full, and keep it in a 140℃ drying oven for 10 hours. After cooling to room temperature, open the reactor, pour out the clear solution, and collect the precipitate at the bottom. Centrifuge the precipitate separately with deionized water and anhydrous ethanol at a speed of 8200 rpm. -1 The mixture was rotated for 15 minutes and then dried in a vacuum drying oven at 70°C for 24 hours to obtain NH4V4O. 10 Nanoribbon precursor.

[0077] 2): Preparation of sulfur-doped NH4V4O 10 Nanoribbon cathode material. Weigh out NH4V4O in a mass ratio of 1:2. 10 Nanoribbon precursors and thiourea were placed on the downwind side of a tube furnace and the upwind side of a tube furnace. After five gas scrubbing cycles, the temperature was raised to 280℃ and held for 5 hours at a gas flow rate of 40 sccm. After cooling, the powder was removed to obtain sulfur-doped NH4V4O. 10 Nanoribbon cathode material.

[0078] Prepared sulfur-doped NH4V4O 10 Nanoribbon cathode materials are used in battery assembly. Sulfur-doped NH4V4O 10 Nanoribbon cathode material, carbon black conductive agent, and polyvinylidene fluoride were thoroughly ground at a mass ratio of 8:1:1, and then NMP solution was added and continuously magnetically stirred for 8 hours. The uniformly dispersed, viscous slurry was coated onto titanium foil and dried in a vacuum drying oven at 80°C for 12 hours. The resulting material was then cut into circular cathode electrode sheets with a diameter of approximately 12 mm, weighed, and set aside. The areal density of the active material on the electrode sheets was 1.5 mg / cm³. -2 Then, the sulfur-doped NH4V4O prepared... 10Nanoribbon cathode material, glass fiber separator, lithium anode, and zinc trifluorosulfonate aqueous electrolyte were used to assemble a 2032 model button zinc-ion battery. 15 μl of electrolyte was added to the cathode side and 10 μl to the anode side. The assembled battery was incubated at 25°C for 12 hours before electrochemical testing. The battery was also equipped with sulfur-doped NH4V4O4. 10 Zinc-ion batteries with nanoribbon cathode materials under different currents (0.2Ag) -1 0.4Ag -1 0.6A g -1 0.8Ag -1 1.0Ag -1 5Ag -1 It exhibited 320.3 mAh g -1 300.4mAh g -1 281.6mA hg -1 263.5mA hg -1 244.3mA hg -1 203.9mA hg -1 The high discharge specific capacity, when the rate recovers to 0.2Ag -1 The capacity can be restored to 315.7mAh g. -1 This demonstrates good rate capability and reversibility, indicating that sulfur-doped NH4V4O 10 Nanoribbon cathode materials possess rapid ion diffusion kinetics and structural stability; according to research results reported by Quan et al., NH4V4O 10 In 5A g -1 The capacity is only 95mAh g -1 .

[0079] Equipped with sulfur-doped NH4V4O 10 Zinc-ion batteries with nanoribbon cathode materials at 10Ag -1 After 5000 cycles at the current density, the capacity retention rate was 87.2%, exceeding most currently reported studies on zinc-ion batteries, indicating that this battery can maintain excellent charge-discharge performance even at high currents. Based on the research results reported by Quan et al., NH4V4O 10 The capacity decay is very severe, at 2A g -1 After 1000 cycles, the capacity retention rate was only about 40%, indicating severe capacity decay.

[0080] Example 8:

[0081] 1): Synthesis of NH4V4O 10Nanoribbon precursor. NH₄VO₃ and oxalic acid monohydrate were dissolved and stirred in ultrapure water at 60°C until the solution became clear and transparent. Ammonia was added dropwise until the pH reached 8.5, and the NH₄VO₃ concentration was 0.08 mol / L. -1 The concentration of oxalic acid monohydrate is 0.1 mol / L. -1 Then transfer the solution to a hydrothermal reactor until it is 80% full, and incubate it in a 160℃ drying oven for 8 hours. After cooling to room temperature, open the reactor, pour out the clear solution, and collect the precipitate at the bottom. Centrifuge the precipitate separately with deionized water and anhydrous ethanol at a speed of 8700 rpm. -1 The mixture was rotated for 4 minutes and then dried in a vacuum drying oven at 60°C for 18 hours to obtain NH4V4O. 10 Nanoribbon cathode material.

[0082] 2): Preparation of sulfur-doped NH4V4O 10 Nanoribbon cathode material. Weigh out NH4V4O in a mass ratio of 1:4. 10 Nanoribbon cathode material and thiourea were placed on the lower air vent side of a tubular furnace, and thiourea on the upper air vent side. After five gas scrubbing cycles, the temperature was raised to 330℃ and held for 5 hours at a gas flow rate of 100 sccm. After cooling, the powder was removed to obtain sulfur-doped NH4V4O. 10 Nanoribbon cathode material.

[0083] Prepared sulfur-doped NH4V4O 10 Nanoribbon cathode materials are used in battery assembly. Sulfur-doped NH4V4O 10 Nanoribbon cathode material, carbon black conductive agent, and polyvinylidene fluoride were thoroughly ground at a mass ratio of 8:1:1. NMP solution was then added and the mixture was continuously stirred magnetically for 8 hours. The uniformly dispersed, viscous slurry was coated onto titanium foil and dried in a vacuum oven at 50°C for 24 hours. The resulting slurry was cut into circular cathode sheets with a diameter of approximately 12 mm, weighed, and set aside. The areal density of the active material on the electrode sheets was 1.5 mg / cm³. -2 Then, the sulfur-doped NH4V4O prepared... 10 Nanoribbon cathode material, glass fiber separator, lithium anode, and zinc trifluorosulfonate aqueous electrolyte were used to assemble a 2032 model button zinc-ion battery. 15 μl of electrolyte was added to the cathode side and 10 μl to the anode side. The assembled battery was incubated at 25°C for 12 hours before electrochemical testing. The battery was also equipped with sulfur-doped NH4V4O4. 10 Zinc-ion batteries with nanoribbon cathode materials under different currents (0.2 A g) -1 0.4Ag -1 0.6Ag -1 0.8Ag -1 1.0Ag-1 5Ag -1 It showed 296.3 mA hg -1 287.1mA hg -1 273.9mA hg -1 258.5mA hg -1 246.0mA hg -1 178.8mA hg -1 The high discharge specific capacity, when the rate recovers to 0.2A g -1 The capacity can be restored to 283.2 mAh g. -1 This demonstrates good rate capability and reversibility, indicating that sulfur-doped NH4V4O 10 Nanoribbon cathode materials possess rapid ion diffusion kinetics and structural stability; according to research results reported by Quan et al., NH4V4O 10 In 5A g -1 The capacity is only 95mAh g -1 .

[0084] Equipped with sulfur-doped NH4V4O 10 Zinc-ion batteries using nanoribbon cathode materials at 10 A g -1 After 5000 cycles at the current density, the capacity retention rate was 83.2%, exceeding most currently reported studies on zinc-ion batteries, indicating that this battery can maintain excellent charge-discharge performance even at high currents. Based on the research results reported by Quan et al., NH4V4O 10 The capacity decay is very severe, at 2A g -1 After 1000 cycles, the capacity retention rate was only about 40%, indicating severe capacity decay.

[0085] Example 9:

[0086] 1): Synthesis of NH4V4O 10 Nanoribbon precursor. NH4VO3 and oxalic acid monohydrate were dissolved and stirred in ultrapure water at 60°C until the solution became clear and transparent. Ammonia was added dropwise until the pH reached 8.0, and the NH4VO3 concentration was 0.15 mol / L. -1 The concentration of oxalic acid monohydrate is 0.3 mol / L. -1 Then transfer the solution to a hydrothermal reactor until it is 80% full, and keep it in a 150°C drying oven for 4 hours. After cooling to room temperature, open the reactor, pour out the clear solution, and collect the precipitate at the bottom. Centrifuge the precipitate separately with deionized water and anhydrous ethanol at a speed of 8500 rpm. -1 The mixture was rotated for 5 minutes and then dried in a vacuum drying oven at 80°C for 12 hours to obtain NH4V4O. 10Nanoribbon precursor.

[0087] 2): Preparation of sulfur-doped NH4V4O 10 Nanoribbon cathode material. Weigh out NH4V4O in a mass ratio of 1:0.5. 10 Nanoribbon precursors and thiourea were placed on the downwind side of a tube furnace and the upwind side of a tube furnace. After five gas scrubbing cycles, the temperature was raised to 340℃ and held for 4 hours at a gas flow rate of 30 sccm. After cooling, the powder was removed to obtain sulfur-doped NH4V4O. 10 Nanoribbon cathode material.

[0088] Prepared sulfur-doped NH4V4O 10 Nanoribbon cathode materials are used in battery assembly. Sulfur-doped NH4V4O 10 Nanoribbon cathode material, carbon black conductive agent, and polyvinylidene fluoride were thoroughly ground at a mass ratio of 8:1:1, and then NMP solution was added and continuously magnetically stirred for 8 hours. The uniformly dispersed, viscous slurry was coated onto titanium foil and dried in a vacuum drying oven at 60°C for 12 hours. The resulting material was cut into circular cathode electrode sheets with a diameter of approximately 12 mm, weighed, and set aside. The areal density of the active material on the electrode sheets was 1.5 mg / cm³. -2 Then, the sulfur-doped NH4V4O prepared... 10 Nanoribbon cathode material, glass fiber separator, lithium anode, and zinc trifluorosulfonate aqueous electrolyte were used to assemble a 2032 model button zinc-ion battery. 15 μl of electrolyte was added to the cathode side and 10 μl to the anode side. The assembled battery was incubated at 25°C for 12 hours before electrochemical testing. The battery was also equipped with sulfur-doped NH4V4O4. 10 Zinc-ion batteries with nanoribbon cathode materials under different currents (0.2 A g) -1 0.4Ag -1 0.6Ag -1 0.8Ag -1 1.0A g -1 5A g -1 It showed 285.6 mA hg -1 273.9mA hg -1 262.8mA hg -1 248.4mA hg -1 235.2mA hg -1 190.5mAh g -1 The high discharge specific capacity, when the rate recovers to 0.2A g -1 The capacity can be restored to 275.6mAh g. -1 This demonstrates good rate capability and reversibility, indicating that sulfur-doped NH4V4O 10Nanoribbon cathode materials possess rapid ion diffusion kinetics and structural stability; according to research results reported by Quan et al., NH4V4O 10 In 5A g -1 The capacity is only 95mAh g -1 .

[0089] Equipped with sulfur-doped NH4V4O 10 Zinc-ion batteries using nanoribbon cathode materials at 10Ag -1 After 5000 cycles at the current density, the capacity retention rate was 78.36%, exceeding most currently reported studies on zinc-ion batteries, indicating that this battery can maintain excellent charge-discharge performance even at high currents. Based on the research results reported by Quan et al., NH4V4O 10 The capacity decay is very severe, at 2Ag -1 After 1000 cycles, the capacity retention rate was only about 40%, indicating severe capacity decay.

[0090] Example 10:

[0091] 1): Synthesis of NH4V4O 10 Nanoribbon precursor. NH₄VO₃ and oxalic acid monohydrate were dissolved and stirred in ultrapure water at 60°C until the solution became clear and transparent. Ammonia was added dropwise until the pH reached 9.6, and the NH₄VO₃ concentration was 0.15 mol / L. -1 The concentration of oxalic acid monohydrate is 0.15 mol / L. -1 Then transfer the solution to a hydrothermal reactor until it is 80% full, and incubate it in a 140℃ drying oven for 4 hours. After cooling to room temperature, open the reactor, pour out the clear solution, and collect the precipitate at the bottom. Centrifuge the precipitate separately with deionized water and anhydrous ethanol at a speed of 8000 rpm. -1 Rotate for 8 minutes, then place in a vacuum drying oven and dry at 70°C for 10 hours to obtain NH4V4O. 10 Nanoribbon precursor.

[0092] 2): Preparation of sulfur-doped NH4V4O 10 Nanoribbon cathode material. Weigh out NH4V4O in a mass ratio of 1:1. 10 Nanoribbon precursors and thiourea were placed on the downwind side of a tube furnace and the upwind side of a tube furnace. After five gas scrubbing cycles, the temperature was raised to 270℃ and held for 4 hours at a gas flow rate of 80 sccm. After cooling, the powder was removed to obtain sulfur-doped NH4V4O. 10 Nanoribbon cathode material.

[0093] Prepared sulfur-doped NH4V4O 10Nanoribbon cathode materials are used in battery assembly. Sulfur-doped NH4V4O 10 Nanoribbon cathode material, carbon black conductive agent, and polyvinylidene fluoride were thoroughly ground at a mass ratio of 8:1:1, and then NMP solution was added and continuously magnetically stirred for 8 hours. The uniformly dispersed, viscous slurry was coated onto titanium foil and dried in a vacuum drying oven at 60°C for 12 hours. The resulting material was cut into circular cathode electrode sheets with a diameter of approximately 12 mm, weighed, and set aside. The areal density of the active material on the electrode sheets was 1.5 mg / cm³. -2 Then, the sulfur-doped NH4V4O prepared... 10 Nanoribbon cathode material, glass fiber separator, lithium anode, and zinc trifluorosulfonate aqueous electrolyte were used to assemble a 2032 model button zinc-ion battery. 15 μl of electrolyte was added to the cathode side and 10 μl to the anode side. The assembled battery was incubated at 25°C for 12 hours before electrochemical testing. The battery was also equipped with sulfur-doped NH4V4O4. 10 Zinc-ion batteries with nanoribbon cathode materials under different currents (0.2 A g) -1 0.4A g -1 0.6A g -1 0.8Ag -1 1.0A g -1 5Ag -1 It showed 307.3 mA hg -1 276.2mA hg -1 245.9mA hg -1 218.4mAh g -1 186.7mAh g -1 126.3mA hg -1 The high discharge specific capacity, when the rate recovers to 0.2Ag -1 The capacity can be restored to 300.4mAh g. -1 This demonstrates good rate capability and reversibility, indicating that sulfur-doped NH4V4O 10 Nanoribbon cathode materials possess rapid ion diffusion kinetics and structural stability; according to research results reported by Quan et al., NH4V4O 10 In 5A g -1 The capacity is only 95mAh g -1 .

[0094] Equipped with sulfur-doped NH4V4O 10 Zinc-ion batteries using nanoribbon cathode materials at 10Ag -1After 5000 cycles at the current density, the capacity retention rate was 76.3%, exceeding most currently reported studies on zinc-ion batteries, indicating that this battery can maintain excellent charge-discharge performance even at high currents. Based on the research results reported by Quan et al., NH4V4O 10 The capacity decay is very severe, at 2A g -1 After 1000 cycles, the capacity retention rate was only about 40%, indicating severe capacity decay.

[0095] Example 11:

[0096] 1): Synthesis of NH4V4O 10 Nanoribbon precursor. NH4VO3 and oxalic acid monohydrate were dissolved and stirred in ultrapure water at 60°C until the solution became clear and transparent. Ammonia was added dropwise until the pH reached 10.0, and the NH4VO3 concentration was 0.07 mol / L. -1 The concentration of oxalic acid monohydrate is 0.14 mol / L. -1 Then transfer the solution to a hydrothermal reactor until it is 80% full, and keep it in a 160℃ drying oven for 10 hours. After cooling to room temperature, open the reactor, pour out the clear solution, and collect the precipitate at the bottom. Centrifuge the precipitate separately with deionized water and anhydrous ethanol at a speed of 7500 rpm. -1 The rotation time was 8 minutes, and the mixture was placed in a vacuum drying oven and dried at 60°C for 18 hours to obtain NH4V4O. 10 Nanoribbon precursor.

[0097] 2): Preparation of sulfur-doped NH4V4O 10 Nanoribbon cathode material. Weigh out NH4V4O in a mass ratio of 1:0.5. 10 Nanoribbon precursors and thiourea were placed on the downwind side of a tube furnace and the upwind side of a tube furnace. After five gas scrubbing cycles, the temperature was raised to 260℃ and held for 2 hours at a gas flow rate of 140 sccm. After cooling, the powder was removed to obtain sulfur-doped NH4V4O. 10 Nanoribbon cathode material.

[0098] Prepared sulfur-doped NH4V4O 10 Nanoribbon cathode materials are used in battery assembly. Sulfur-doped NH4V4O 10 Nanoribbon cathode material, carbon black conductive agent, and polyvinylidene fluoride were thoroughly ground at a mass ratio of 8:1:1, and then NMP solution was added and continuously magnetically stirred for 8 hours. The uniformly dispersed, viscous slurry was coated onto titanium foil and dried in a vacuum drying oven at 60°C for 14 hours. The resulting material was cut into circular cathode electrode sheets with a diameter of approximately 12 mm, weighed, and set aside. The areal density of the active material on the electrode sheets was 1.5 mg / cm³. -2 Then, the sulfur-doped NH4V4O prepared...10 Nanoribbon cathode material, glass fiber separator, lithium anode, and zinc trifluorosulfonate aqueous electrolyte were used to assemble a 2032 model button zinc-ion battery. 15 μl of electrolyte was added to the cathode side and 10 μl to the anode side. The assembled battery was incubated at 25°C for 12 hours before electrochemical testing. The battery was also equipped with sulfur-doped NH4V4O4. 10 Zinc-ion batteries with nanoribbon cathode materials under different currents (0.2Ag) -1 0.4Ag -1 0.6A g -1 0.8Ag -1 1.0Ag -1 5Ag -1 It showed 296.7 mA hg -1 273.2mAh g -1 250.4mAh g -1 233.8mAh g -1 205.6mA hg -1 135.9mA hg -1 The high discharge specific capacity, when the rate recovers to 0.2Ag -1 The capacity can be restored to 285.7mAh g. -1 This demonstrates good rate capability and reversibility, indicating that sulfur-doped NH4V4O 10 Nanoribbon cathode materials possess rapid ion diffusion kinetics and structural stability; according to research results reported by Quan et al., NH4V4O 10 In 5A g -1 The capacity is only 95mAh g -1 .

[0099] Equipped with sulfur-doped NH4V4O 10 Zinc-ion batteries using nanoribbon cathode materials at 10 A g -1 After 5000 cycles at the current density, the capacity retention rate was 73.22%, exceeding most currently reported studies on zinc-ion batteries, indicating that this battery can maintain excellent charge-discharge performance even at high currents. Based on the research results reported by Quan et al., NH4V4O 10 The capacity decay is very severe, at 2Ag -1 After 1000 cycles, the capacity retention rate was only about 40%, indicating severe capacity decay.

[0100] The technical solutions disclosed and proposed in this invention can be implemented by those skilled in the art by appropriately modifying the conditions and routes, etc. Although the methods and preparation techniques of this invention have been described through preferred embodiments, those skilled in the art can obviously modify or recombine the methods and technical routes described herein without departing from the content, spirit, and scope of this invention to achieve the final preparation technique. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art and are considered to be included within the spirit, scope, and content of this invention.

Claims

1. Sulfur-doped NH4V4O for use in aqueous zinc-ion batteries 10 Nanoribbon cathode materials; characterized by... Ammonium vanadate contains both sulfate ion groups and oxygen vacancies within its structure. The sulfidation process incorporates sulfur and sulfate ions into the interlayer space of ammonium vanadate, which act as interlayer pillars to support the layered structure of ammonium vanadate and expand the interlayer spacing, providing a wide ion channel for the transport of zinc ions. The reducing sulfur gas generated during sulfidation introduces oxygen vacancies into the interior of ammonium vanadate.

2. The sulfur-doped NH4V4O for aqueous zinc-ion batteries according to claim 1 10 A method for preparing nanoribbon cathode materials, characterized by: Includes the following steps: 1): Preparation of NH4V4O 10 Nanoribbon precursor: Weigh NH4VO3 powder and oxalic acid monohydrate granules and dissolve them in deionized water. Stir under water bath heating until the solution is clear and transparent. After the solution is allowed to stand and cool, ammonia water is added dropwise and the pH is adjusted to 8.0~10.0 using a pH meter. Then, the mixed solution is transferred to a hydrothermal reactor and placed in a forced-air drying oven for hydrothermal treatment for 4~12 hours. After naturally cooling to room temperature, the hydrothermal reactor is opened, the supernatant is poured out, and the precipitate at the bottom of the reactor is collected. The precipitate is washed with water and ethanol respectively, and then thoroughly dried in a vacuum drying oven to obtain NH4VO3. 10 Nanoribbon precursors; 2): Preparation of sulfur-doped NH4V4O 10 Nanoribbon cathode material: Weigh the NH4V4O obtained in step 1). 10 The nanoribbon precursor was placed on one side of an alumina boat, while thiourea powder was placed on the other side. The boat was then capped and placed inside a tube furnace, with one side of the thiourea powder facing upwind and the other downwind. The tube furnace was then purged to fill it with an inert atmosphere, which was continuously circulated. After the furnace cooled naturally, the sulfur-doped NH4V4O2 was removed. 10 Nanoribbon cathode material.

3. The preparation method according to claim 2, characterized in that, In step 1), the molar ratio of raw material NH4VO3 to oxalic acid monohydrate is 1:0.8~2; after dissolving in deionized water, the concentration of NH4VO3 is 0.05~0.15 mol L. -1 .

4. The preparation method according to claim 2, characterized in that, In step 1), the hydrothermal temperature is 140~180 ℃, and the hydrothermal time is maintained for 4~12 h after the temperature is raised to the specified temperature.

5. The preparation method according to claim 2, characterized in that, In step 1), the centrifuge speed for washing the precipitate is 7500 r / min. -1 The centrifugation time for each cycle should be at least 3 minutes.

6. The preparation method according to claim 2, characterized in that, In step 1), the vacuum drying temperature is above 40 ℃, and the drying time is at least 8 hours.

7. The preparation method according to claim 2, characterized in that, In step 2), thiourea: sulfur-doped NH4V4O 10 The mass ratio of the nanoribbon cathode material is 0.5~4:1, and the calcination atmosphere is ammonia or nitrogen.

8. The preparation method according to claim 2, characterized in that, In step 2), the gas flow rate during calcination is controlled below 200 sccm, the tube furnace holding temperature is 260~350 ℃, and the holding time is more than 1 h.

9. The sulfur-doped NH4V4O for aqueous zinc-ion batteries according to claim 1 10 Applications of nanoribbon cathode materials; characterized by... Prepared sulfur-doped NH4V4O 10 Nanoribbon cathode materials are used in battery assembly. The obtained cathode material is mixed with carbon black conductive agent and polyvinylidene fluoride in a certain proportion to form a uniform slurry, which is then coated on titanium foil and cut into circular cathode electrode sheets, separators and lithium sheets for assembling button batteries.

Citation Information

Patent Citations

  • Novel preparation method of silver sulfate doping silver vanadate composite photocatalysts

    CN106000425A

  • Nanorod-like vanadium tetrasulfide powder and preparation method and application thereof

    CN110282660A